Correlation between Estradiol and Progesterone Hormone Levels and Endometrial Thickness, Pattern, and Vascularization in Patients Undergoing In Vitro Fertilization - Afrilia, Inayah; Hendry, Dedy (Andalas Obstetrics And Gynecology Journal, 2023)
Introduction: Currently there is a shift in trends in in vitro fertilization programs related to embryo transfer. Embryo transfer is largely determined by the window of implantation related to endometrial receptivity. Endometrial pattern, thickness and vascularity are biomarkers of endometrial receptivity. Estrogen and progesterone are known to have a role in the development of this biomarker.Methods: This study used a cross-sectional design. The study was conducted from January to December 2022 at the Morula IVF Fertility Clinic Padang, RSU Bunda Medical Center (BMC) Padang.Results: At the end of the study, there were 100 respondents with an average age of 25-29 years, most of them were overweight, and almost all of them had primary infertility, and the average duration of infertility was 6.75 ± 3.98 years. At the time of ovulation trigger, the mean estradiol levels were 3070.32 ± 1186.985 pg/ml, progesterone 1.10 ± 0.57 ng/ml, and E2/P4 ratio 3.64 ± 3.10. Most of the respondents had type A endometrial pattern, type I vascularity, and the mean endometrial thickness was 11.58 ± 2.94 mm. There is a statistically significant relationship between estradiol and endometrial thickness and vascularity. In addition, a relationship was also found between progesterone and E2/P4 with endometrial vascularization. However, there is no significant relationship between progesterone and the E2/P4 ratio with the endometrial pattern.Conclusion: Estrogen, progesterone and E2/P4 are related to endometrial vascularization and estrogen is related to thickness. None of these hormones are associated with endometrial pattern.